Changing structure of low income housing provision in Malaysia: housing allocation under the computerised Open Registration System (ORS) for low cost house buyer - Shuid, Syafiee (2009)
Malaysia is one of the countries in East Asia that has experience the rapid economic growth during the early 1990s before suffered the severe downturn during the Asian Financial Crisis in 1997-1998. Following the crisis, the property sector particularly housing have badly affected and required federal government intervention to revive the economy through provision of low income housing. Nevertheless the state intervention in low income housing provision is against the practice in other East Asian countries which generally moving towards market economy as propagated by International Monetary Fund (IMF). Low income housing provision by the federal government also earmarked changes in structure of low income housing provision in Malaysia including the allocation of the houses to eligible buyers. Using Structure of Housing Provision (SHP) approach developed by Michael Ball and Harloe as framework to analyse the changes in low income housing provision in Malaysia. The paper then will discuss the role played by the state in housing allocation for the poor using the Computerised Open Registration System (ORS) for low cost houses provided by the state and market.